Impacts of the Corporate Sustainability Due Diligence Directive (CSDDD) ‒ A Supply Chain and Competition perspective - Kortelainen, Silja (My University, 2022)
The growth of international supply chains has brought significant benefits but has also had serious negative impacts in terms of human rights and environmental violations. Although voluntary initiatives and guidelines have been widely developed for the use companies, they have not led to the desired improvements in supply chain sustainability for many companies. Both the European Union and individual EU Member States have sought to fill this accountability gap by introducing various due diligence obligations. However, these existing national or EU-level obligations always focus on either a specific sector, issue or country. NGOs and trade unions, as well as certain large multinational companies, have started to call for mandatory EU-level legislation to extend the due diligence for human rights and the environment to all sectors and commodities. On February 2022, the European Commission published a legislative proposal for EU-wide regulation on supply chain due diligence: the Corporate Sustainability Due Diligence Directive (CSDDD). The proposal aims to promote sustainable business activities in global supply chains as well as harmonize business environment for companies operating in the Union. Many scholars expect mandatory due diligence to be an effective means of tackling human rights and environmental abuses. However, the impacts of the directive on supply chains and their management as well as on the competitiveness of companies has received less attention. This study aims to contribute to filling this research gap. The research has been carried out as a mix-methods study using the Delphi method. It involved ten supply chain or sustainability experts from Finnish companies as well as advocacy organisations and NGOs. The results of the research show that the directive is likely to increase the complexity of supplier governance and pose challenges for many companies. Difficulties are expected to arise in controlling and monitoring supply chains, obtaining reliable information from supply chain partners and reporting sustainability issues properly. Experts anticipate it to be particularly demanding to ensure that sub-suppliers comply with the due diligence requirements. Moreover, implementing and complying with the CSDDD is considered to be challenging largely due to a lack of know-how and collaboration along supply chains. The directive is expected to lead to higher costs for supply chain management and many companies may have to change their procurement strategy and increase the prices of their products. It is therefore expected that in the short to medium term, the competitiveness of the companies covered by the directive is likely to deteriorate in the global market. In the long term, however, competitiveness may improve. In the internal market, the business environment is expected to become more unified, and European companies not covered by the directive, such as SMEs, are not considered to weaken the competitive position of companies affected by the law, especially in the long term. Ultimately, however, the companies that are estimated to benefit most from the new directive are those that have already started sustainability efforts and voluntarily set sustainability requirements for their supply chains. In the short term in particular, these companies are expected to become more competitive. In the long run, the lead of the frontrunners is likely to remain, but it is expected to level off.

Kansainvälisten toimitusketjujen kasvu on tuonut huomattavia etuja, mutta sillä on ollut myös vakavia negatiivisia vaikutuksia ihmisoikeus- ja ympäristörikkomuksiin liittyen. Vaikka vapaaehtoisesti noudatettavia ohjeita on kehitetty laajasti yritysten käyttöön, ne eivät ole monien yritysten kohdalla johtaneet toivottuihin parannuksiin toimitusketjujen vastuullisuuden osalta. Sekä Euroopan unioni että yksittäiset EU-jäsenmaat ovat pyrkineet täyttämään tämän vastuuvelvollisuuden puutteen ottamalla käyttöön erilaisia huolellisuusvelvoitteita. Näissä jo olemassa olevissa kansallisissa tai EU-tason velvoitteissa keskitytään kuitenkin aina joko tiettyyn sektoriin, ongelmakohtaan tai maahan. Kansalaisjärjestöt, ammattiliitot ja suuret monikansalliset yritykset ovat alkaneet vaatia pakollista EU-tason lainsäädäntöä, jolla ihmisoikeuksia ja ympäristöä koskeva huolellisuusvelvoite ulotetaan koskemaan kaikkia aloja ja hyödykkeitä. Euroopan Komissio julkaisi helmikuussa 2022 lainsäädäntöehdotuksen EU:n laajuisesta yritysten kestävää toimintaa koskevasta huolellisuusvelvoitedirektiivistä. Ehdotuksen tavoitteena on edistää vastuullista liiketoimintaa globaaleissa toimitusketjuissa sekä harmonisoida unionissa toimivien yritysten liiketoimintaympäristöä. Useat tutkijat odottavat pakollisen huolellisuusvelvoitteen olevan tehokas keino puuttua ihmisoikeus- ja ympäristörikkomuksiin. Se, miten direktiivi tulee vaikuttamaan toimitusketjuihin ja niiden johtamiseen sekä yritysten kilpailukykyyn, on jäänyt vähemmälle huomiolle. Tämä tutkimus pyrkii osaltaan täyttämään kyseisen tutkimusaukon. Tutkimus on toteutettu monimenetelmätutkimuksena Delfoi-menetelmää hyväksi käyttäen. Siihen osallistui kymmenen toimitusketjujen tai kestävän kehityksen asiantuntijaa suomalaisista yrityksistä sekä etu- ja kansalaisjärjestöistä. Tutkimuksen tulokset osoittavat, että direktiivin seurauksena toimittajien hallinnan monimutkaisuus todennäköisesti lisääntyy ja aiheuttaa haasteita monille yrityksille. Vaikeuksia aiheuttavat luultavasti toimitusketjujen kontrollointi ja valvonta, luotettavan tiedon saaminen toimitusketjun yhteistyökumppaneilta ja kestävyysasioiden asianmukainen raportointi. Erityisen vaativaa on asiantuntijoiden mukaan valvoa, että alihankkijat noudattavat huolellisuusvelvoitteen asettamia vaatimuksia. Velvoitteen implementoinnin ja noudattamisen haasteellisuuden nähdään johtuvan pitkälti myös osaamisen ja yhteistyön puutteista toimitusketjuissa. Arvioidaan, että direktiivi tulee aiheuttamaan korkeampia kustannuksia toimitusketjujen johtamiselle ja monien yritysten on muutettava hankintastrategiaansa sekä nostettava tuotteidensa hintoja. Näin ollen on odotettavissa, että lyhyellä ja keskipitkällä aikavälillä direktiivin soveltamisalaan kuuluvien yritysten kilpailukyky todennäköisesti heikkenee globaaleilla markkinoilla. Pitkällä aikavälillä kilpailukyky voi kuitenkin parantua. Sisämarkkinoilla liiketoimintaympäristön odotetaan muuttuvan yhtenäisemmäksi, eikä direktiivin soveltamisalan ulkopuolelle jäävien eurooppalaisten yritysten, kuten pk-yritysten, katsota heikentävän lain soveltamisalaan kuuluvien yritysten kilpailuasemaa varsinkaan pitkällä aikavälillä. Lopulta uuden direktiivin arvioidaan hyödyttävän kuitenkin eniten niitä yrityksiä, jotka ovat jo aloittaneet kestävyystoimet ja asettaneet vapaaehtoisesti kestävyysvaatimuksia toimitusketjuilleen. Etenkin lyhyellä aikavälillä näiden yritysten kilpailukyvyn odotetaan paranevan. Edelläkävijöiden etumatka säilyy todennäköisesti myös pidemmällä aikavälillä, mutta sen odotetaan tasaantuvan.
Keywords: due diligence, sustainability, supply chains, EU, legislation, supply chain management, corporate responsibility